2018
DOI: 10.1039/c8cc07405d
|View full text |Cite
|
Sign up to set email alerts
|

Spiro-fused bis-hexa-peri-hexabenzocoronene

Abstract: A spiro-fused hexa-peri-hexabenzocoronene dimer is first prepared, which is confirmed by X-ray crystallography, exhibiting reversible redox property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…[36] Hexa-peri-hexabenzocoronene (HBC), with a pronounced self-assembly and high intrinsic charge-carrier mobility, has been reported by Muellen et al [38] This group has further demonstrated the efficient synthesis of a spiro-fused HBC dimer (compound 35, Scheme 14) with robust orthogonally arranged spiro-linked HBC structures. [39] Noteworthily, adjacent compound 35 molecules are stacked by π-π overlaps of HBC subunits, with intermolecular distances ranging from 3.42 to 3.63 Å ( Figure 5). Compared with its HBC counterpart, compound 35 exhibited a similar but less structured absorption pattern, along with a two-fold enhanced absorption behavior and a marginally redshifted absorption maximum.…”
Section: Other Extensions Of Condensed Spirobifluorenesmentioning
confidence: 99%
“…[36] Hexa-peri-hexabenzocoronene (HBC), with a pronounced self-assembly and high intrinsic charge-carrier mobility, has been reported by Muellen et al [38] This group has further demonstrated the efficient synthesis of a spiro-fused HBC dimer (compound 35, Scheme 14) with robust orthogonally arranged spiro-linked HBC structures. [39] Noteworthily, adjacent compound 35 molecules are stacked by π-π overlaps of HBC subunits, with intermolecular distances ranging from 3.42 to 3.63 Å ( Figure 5). Compared with its HBC counterpart, compound 35 exhibited a similar but less structured absorption pattern, along with a two-fold enhanced absorption behavior and a marginally redshifted absorption maximum.…”
Section: Other Extensions Of Condensed Spirobifluorenesmentioning
confidence: 99%
“…Two main strategies for fabricating molecular NGs, with defined chemical structures, have been developed in recent years. On one hand, oxidative cyclodehydrogenation of custom-made polycyclic aromatic hydrocarbons (PAHs) and, on the other hand, on-surface cyclodehydrogenation have evolved into powerful and groundbreaking strategies for the preparation of atomically precise molecular NGs. To this end, the 13 fused-benzene rings of hexa- peri -hexabenzocoronene (HBC), which are arranged in a 2D disk-shaped fashion, render HBCs the smallest graphene fragment. Driven by its tendency to π–π stacking, highly ordered columnar stacks of HBCs have been exploited for several applications. , …”
Section: Introductionmentioning
confidence: 99%
“…However, modification of 9,9′‐spirobifluorene has mainly focused on the singly core‐substitution at different reaction positions, and studies that explored extension of the spiro‐π‐systems via annulation, which could increase intermolecular π•••π overlap area by expanded rigid spiroconjugation in the solid state, are rather limited. [ 19–28 ]…”
Section: Figurementioning
confidence: 99%
“…However, modification of 9,9′-spirobifluorene has mainly focused on the singly core-substitution at different reaction positions, and studies that explored extension of the spiro-π-systems via annulation, which could increase intermolecular π•••π overlap area by expanded rigid spiroconjugation in the solid state, are rather limited. [19][20][21][22][23][24][25][26][27][28] Halogenation has been an important chemical modification means applied in constructing various organic semiconductors such as fluorination and chlorination. [29][30] Compared to fluorination that has been well-studied, the chlorination strategy has not been extensively investigated as the larger atomic size of chlorine results in steric effects in conjugated backbones.…”
mentioning
confidence: 99%